L’inclusion du Black feminism dans la philosophie politique: une approche féministe de la décolonisation des savoirs - Berthelot-Raffard, Agnès (Recherches féministes, 2018)
Fondé sur ce que l’autrice nomme l’« approche féministe de la décolonisation des savoirs », cet article aborde la place du féminisme noir dans la philosophie politique. L’autrice montre que la pensée féministe noire est une philosophie de la justice sociale. À partir de la notion de « modestie épistémique » proposée par Eva Feder Kittay, l’autrice examine comment l’ignorance du système de valeurs et des expériences des femmes noires dans les théories libérales constitue une injustice herméneutique pour les intellectuelles qui édifient le Black feminism comme théorie de la justice raciale et de genre.
Keywords: afro-féminisme; amériques; approches et analyses; belgique; black feminism; canada; care; cours; discipline; europe; europe francophone; france; féminisme décolonial; féminismes noirs; histoire et politique; injustices herméneutiques; justice sociale; philosophie; philosophie politique; pol4212; premier cycle; québec; régions géographiques; sciences humaines; suisse; thématiques; éthique

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."–The publisher.
Le chapitre 22 de Miranda Fricker et Katharine Jenkins, “Epistemic injustice, ignorance, and trans experiences” a été donné en lecture au cours FEM9000.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Luttes féministes autour du consentement: Héritages et impensés des mobilisations contemporaines sur la gynécologie - Quéré, Lucile (Nouvelles Questions Féministes, 2016)
L'étude des mobilisations françaises de l'année 2014-2015 autour de la gynécologie permet d'interroger les différentes manières dont les mouvements féministes se sont saisis de la notion de consentement. Théorisé par les féministes à propos de la sexualité, le consentement est apparu comme un des principes fondateurs d'une morale sexuelle féministe. Les mouvements de 2014, portés par des militantes de la cause des femmes, (ré)introduisent cette notion dans le cabinet médical, et l'appliquent notamment à l'interaction gynécologique. Cela leur permet d'utiliser la loi française de 2002 sur les droits des patient·e·s comme un outil de politisation du cabinet gynécologique et de remise en cause des pratiques et des discours des soignant·e·s à l'égard des femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; cours; discipline; discours dominant; europe; france; inégalités; justice sociale; militance; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; santé; santé des femmes*; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques

Traite, prostitution, inégalité - MacKinnon, Catharine A. (M éditeur, 2014)
De nos jours, il n'y a pas plus de prise de position favorable à la traite des êtres humains à des fins d'exploitation sexuelle qu'il y a de prise de position publique pour l'esclavage. Il est également très difficile de trouver des partisanes déclarées de l'inégalité… Ce n'est pourtant pas le cas de la prostitution. Certaines personnes sont pour la prostitution. Plus nombreuses sont celles qui considèrent politiquement correct de la tolérer. La plupart présument que, même si elle n'est pas réellement souhaitable, la prostitution est nécessaire, inévitable et sans dommage. Est-ce que la décriminalisation du proxénétisme et la légalisation des maisons closes assureront une plus grande sécurité physique aux personnes prostituées ? Contrairement à la Cour suprême du Canada, la juriste de réputation mondiale, Catharine A. Mac- Kinnon, répond négativement à cette question. Elle soutient que « loin de rendre la vie des prostituées plus sûre, la décriminalisation totale de la prostitution peut même la rendre encore plus dangereuse ». Pour cela, elle s'appuie sur les expériences des pays qui ont légalisé la prostitution et le proxénétisme et sur celles des pays, de plus en plus nombreux, qui décriminalisent les personnes prostituées et pénalisent les clients-prostitueurs ; la stigmatisation liée à l'activité Prostitutionnelle se retourne désormais contre ceux qui en profitent : les prostitueurs et les proxénètes.
Section: 123 pages ; 18 cm.
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; droits des femmes*; inégalités; justice sociale; patriarcat; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; travail du sexe-prostitution; violences

Feminist, queer, crip - Kafer, Alison (Indiana University Press, 2013)
Select all Front Matter (pp. i-vi) Front Matter (pp. i-vi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.1 Table of Contents (pp. vii-viii) Table of Contents (pp. vii-viii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.2 Acknowledgments (pp. ix-xii) Acknowledgments (pp. ix-xii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.3 Textual Description of the Cover Art (pp. xiii-xvi) Textual Description of the Cover Art (pp. xiii-xvi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.4 Introduction: Imagined Futures (pp. 1-24) Introduction: Imagined Futures (pp. 1-24) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.5 I have never consulted a seer or psychic; I have never asked a fortune-teller for her crystal ball. No one has searched my tea leaves for answers or my stars for omens, and my palms remain unread. But people have been telling my future for years. Of fortune cookies and tarot cards they have no need: my wheelchair, burn scars, and gnarled hands apparently tell them all they need to know. My future is written on my body. In 1995, six months after the fire, my doctor suggested that my thoughts of graduate school were premature, if not misguided. He... 1 Time for Disability Studies and a Future for Crips (pp. 25-46) 1 Time for Disability Studies and a Future for Crips (pp. 25-46) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.6 What would it mean to explore disability in time or to articulate “crip time”? Temporal categories are already commonly used in formulations of disability; one aspect of cripping time might simply be to map the extent to which we conceptualize disability in temporal terms. The medical field in particular has a long tradition of describing disability in reference to time. “Chronic” fatigue, “intermittent” symptoms, and “constant” pain are each ways of defining illness and disability in and through time; they describe disability in terms of duration. “Frequency,” “incidence,” “occurrence,” “relapse,” “remission”: these, too, are the time frames of symptoms, illness,... 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.7 In thinking about crip futurity, I find myself haunted by Ashley X. Born in 1997, the girl known as Ashley X was diagnosed with “static encephalopathy” a few months after her birth. “In the ensuing years,” doctors note, “her development never progressed beyond that of an infant,” and her doctors held no hope that her cognitive or neurological baseline would improve.¹ “At the age of 6 years, she [could] not sit up, ambulate, or use language.”² Concerned about their daughter’s long-term future, Ashley’s parents met with doctors in 2004 to discuss the potential effects of puberty and physical growth on... 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.8 The pervasiveness of prenatal testing, and especially its acceptance as part of the standard of care for pregnant women, casts women as responsible for their future children’s able-bodiedness/able-mindedness; prospective parents are urged to take advantage of these services so as to avoid burdening their future children with any disabilities.¹ This notion of “burdening” children finds an echo in the debate over same-sex marriage, with LGBT couples cast as selfish parents, placing their own desires over the physical and mental health of their children (and, by extension, of all children). Moreover, according to Timothy Dailey of the Family Research Council, homosexual... 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.9 “Super man,” the billboard exclaims, the unfamiliar gap between the two words emphasizing both the noun and its adjective. Below this phrase is the word “STRENGTH,” followed by the imperative “Pass It On.” At the bottom, in small print, runs the name and web address of the organization behind this public relations campaign: Values.com/Foundation for a Better Life. The “super man” referenced in the caption is, of course, the late Christopher Reeve, the white actor who starred in a series ofSupermanfilms in the 1980s before becoming a quadriplegic in a riding accident in 1995. A black-and-white photograph of... 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.10 Controversy came quickly to the cyborg. In 1983,Socialist Reviewinvited several feminist theorists, among them Donna Haraway, “to write about the future of socialist feminism in the context of the early Reagan era.”¹ Haraway responded with “A Manifesto for Cyborgs,” framing the cyborg as a figure of feminist critique.² Her cyborg was a radical border-crosser, blurring the boundaries between human and animal, machine and organism, physical and non-physical.³ Such a cyborg, she argued, could “guide us to a more livable place,” an “elsewhere,” in which “people are not afraid of their joint kinship with animals and machines, not afraid... 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.11 Although concern with the environment has long been an animating force in disability studies and activism, “environment” in this context typically refers to the built environment of buildings, sidewalks, and transportation technologies. Indeed, the social model of disability is premised on concern for the built environment, stressing that people are disabled not by their bodies but by their inaccessible environments. (The wheelchair user confronting a flight of steps is probably the most common illustration of this argument.) Yet the very pervasiveness of the social model has prevented disability studies from engaging with the wider environment of wilderness, parks, and nonhuman... 7 Accessible Futures, Future Coalitions (pp. 149-170) 7 Accessible Futures, Future Coalitions (pp. 149-170) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.12 When describing disability studies to my students, I often draw on Douglas Baynton’s insight that “disability is everywhere in history once you begin looking for it.”¹ For Baynton, “looking for it” entails not only recovering the stories of disabled people or tracing histories of disability discrimination but also exploring how notions of disability and able-mindedness/able-bodiedness have functioned in different contexts. Baynton issues his provocation to historians, but disability studies scholars in other fields have extended its reach, pushing their own colleagues to recognize disability as a category of analysis. Deeply influenced by and indebted to this work, I use this... Appendices (pp. 171-178) Appendices (pp. 171-178) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.13 Notes (pp. 179-224) Notes (pp. 179-224) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.14 Bibliography (pp. 225-252) Bibliography (pp. 225-252) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.15 Index (pp. 253-258) Index (pp. 253-258) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.16 Back Matter (pp. 259-259) Back Matter (pp. 259-259) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.17 Indiana University Press logo Front Matter Download XML Table of Contents Download XML Acknowledgments Download XML Textual Description of the Cover Art Download XML Introduction:: Imagined Futures Download XML Time for Disability Studies and a Future for Crips Download XML At the Same Time, Out of Time:: Ashley X Download XML Debating Feminist Futures:: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians Download XML A Future for Whom?: Passing on Billboard Liberation Download XML The Cyborg and the Crip:: Critical Encounters Download XML Bodies of Nature:: The Environmental Politics of Disability Download XML Accessible Futures, Future Coalitions Download XML Appendices Download XML Notes Download XML Bibliography Download XML Index Download XML Back Matter Download XML ABOUT US About JSTOR Mission and History JSTOR Labs JSTOR Daily News Webinars Careers EXPLORE CONTENT What's in JSTOR Advanced Search By Subject By Title Collections Publisher Images RESEARCH TOOLS Data for Research The JSTOR Understanding Series Constellate HELP CENTER Get Support Get Access LibGuides Research Basics Contact Us For Librarians For Publishers Teaching Resources JSTOR is part of ITHAKA, a not-for-profit organization helping the academic community use digital technologies to preserve the scholarly record and to advance research and teaching in sustainable ways.©2000‍–2024 ITHAKA. All Rights Reserved. JSTOR®, the JSTOR logo, JPASS®, Artstor®, Reveal Digital™ and ITHAKA® are registered trademarks of ITHAKA. Terms & Conditions of Use Privacy Policy Accessibility Cookie Policy Cookie Settings Description In Feminist, Queer, Crip Alison Kafer imagines a different future for disability and disabled bodies. Challenging the ways in which ideas about the future and time have been deployed in the service of compulsory able-bodiedness and able-mindedness, Kafer rejects the idea of disability as a pre-determined limit. She juxtaposes theories, movements, and identities such as environmental justice, reproductive justice, cyborg theory, transgender politics, and disability that are typically discussed in isolation and envisions new possibilities for crip futures and feminist/queer/crip alliances. This bold book goes against the grain of normalization and promotes a political framework for a more just world.
Section: xiii, 258 pages : illustrations ; 23 cm
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; care; corps; cours; crip; discipline; future; identités LGBTQIA2+; intersectionnalité; justice sociale; philosophie; premier cycle; périodes historiques; queer; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1920; thématiques; études critiques du handicap

Care, justice et dépendance : introduction aux théories du care - Garrau, Marie; Goff, Alice Le (Presses Universitaires de France, 2010)
Ce livre retrace le parcours théorique de la notion de dépendance dans la philosophie féministe contemporaine, de la critique du fonctionnement du concept dans la rhétorique de l’État libéral aux modalités de son inclusion dans une théorie de la justice. Deux axes se dégagent, qui convergent dans une tentative de redéfinition de la notion d’autonomie : les relations de dépendance constituent le point de départ de l’éthique du « care » ou de la sollicitude, qu’il s’agira de présenter ici ; elles ont en outre suscité des reformulations importantes des théories de la justice sur la base d’une anthropologie politique qui cherche à prendre acte de la constitution relationnelle des agents moraux. L’enjeu de ces réflexions n’est donc pas simplement de réévaluer la notion de dépendance, mais aussi de fournir un fondement normatif à l’inclusion des personnes dépendantes dans la communauté morale et politique, voire d’élaborer une conception renouvelée de la citoyenneté.
Keywords: approches et analyses; autonomie; capitalisme; care; discipline; justice sociale; philosophie; politiques néolibérales; projet charge mentale; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; théorie du care